Pengaruh Kualitas Laporan Keberlanjutan dan Risiko pada Profitabilitas Perusahaan - Anak Agung Ananda Satwika (Universitas 45 Surabaya, 2023)
Sustainability is an issue that has received considerable attention recently. Publication of sustainability reports is also becoming a trend in Indonesia. This research was conducted to determine whether there is an influence by the quality of sustainability reports and risks on company profitability. The company's profitability is measured using the net profit margin. The quality of sustainability reports is measured using a model developed by Al-Shaer and Zaman (2016). Risk is measured using the company's stock beta. Companies listed on the IDX ESG Leaders index for the 2020-2022 period are used as sample. Result shows that the quality of sustainability reports has a positive effect on profitability but risk has no effect on profitability. The research results can be used as a guideline for investors who wish to invest in companies included in the IDX ESG Leaders index..